Assessment of prognosis in patients with stage II colon cancer - Martins, Patrícia; Martins, Sandra (Journal of Coloproctology, 2015)
Pathologic staging is currently the most important prognostic factor in colon cancer, although individually this procedure does not provide a complete clinical outcome.This study aimed to determine the disease-specific survival of patients with colon cancer treated in the Braga Hospital from January 2005 to December 2013, according to the American Joint Committee on Cancer, 6th edition, and the disease-free survival and disease-specific survival of high- and low-risk stage II patients, whether in use, or not, of adjuvant chemotherapy.We obtained a total sample of 578 patients, with 145 and 65 high- and low-risk stage II patients, respectively. We observed a 5-year disease-specific survival rate of 93%, 27.4% and 75% for stage IIA, IIB and IIIA patients, respectively, where IIIA and IIB present statistically significant differences (p = 0.001). In high-risk stage II patients, disease-free survival (p = 0.107) and disease-specific survival (p = 0.037) were higher in the group submitted to chemotherapy. In low- risk patients, disease-free survival was higher in the group submitted to chemotherapy (p = 0.494), while disease-specific survival was lower (p = 0.426).The differences observed between stage IIB and IIIA survival can be explained by the consensual use of adjuvant chemotherapy in stage IIIA, and by its controversial use in stage IIB. Adjuvant chemotherapy showed to be effective only in high-risk stage II patients in terms of disease-specific survival.In the future, other markers, namely molecular ones, may be used to stratify the risk of stage II patients and determine who will benefit from adjuvant chemotherapy.
Keywords: Colon cancer; High- and low-risk stage II; Disease-free survival; Disease-specific survival